Feasibility study of Community Life Healthcare Corporation - Ocampo, Shierly (College of Engineering, 2005)
Community Life Healthcare Corporation (CLHC) is a Health Maintenance Organization (HMO) that aims to provide health benefits to the self-employed populace of National Capital Region (NCR). PhilHealth offers health plans nationwide with priority on the indigent group. And a number of HMOs are operating in the country but their target market is the high-income class which leaves the health insurance need of the self-employed unattended. These self-employed people are neither too rich to afford the premiums offered by the usual HMOs nor too poor to be prioritized by the government. To determine the demand for this service, data from National Statistics Office, PhilHealth, and other relevant organizations are gathered. The 2004 market on NCR is about 422707 persons but PhilHealth's 2004 paying enrollees for NCR is only 216,400. And, other HMOs self-employed members are 45,450. These combined enrollees of the competitors equate to 62% market share. The unsatisfied demand of more than 160,800 Filipinos or 38% of the market in NCR is worth the marketing effort CLHC would spend. The target is segmented into three groups: the transport group, food and market sales workers, and shops and personal service providers. The company designs an extensive marketing strategy to reach these different segments. The company would create a marketing department composed of the seminar team, community development team, and the advertising team. Also, the different associations would be reached and they would be given a percentage from the stockholders equity depending on the number of members they can enroll to CLHC. In addition to this, prices of the premiums are adjusted to suit the paying capacity of individuals. Although premiums are affordable, benefits are guaranteed to be satisfactory and can be easily accessed especially in case of emergency. The collection of payment would also be easy to the members since CLHC would hire collecting agents who would do house to house collection during the due dates. Some bayad centers and banks in different cities would also be collecting partners. These would all be under the two service processes which are benefit claiming process and collecting process. In putting up a Health and Maintenance Organizations, there would be several requirements. One of these is the input requirements. These include one of the most important input required which is the benefit package. This includes the list of all the benefits that the members are entitled depending on the premium they are paying. Also, this states that the member should pay for the policy for five straight years. In turn, the member together with two dependents would be insured for the span of ten years. Other input requirements are paper materials which will be needed in making the application form, claim form, benefit payment notice, brochures, contracts, and membership cards. The list of providers is also a requirement. There would be different health providers in Marikina City, Muntinlupa City, Manila City, Quezon City, Parafiaque City, Mandaluyong City, Makati City, Malabon, Pasig City, Caloocan City, Las Pinas City. The main building would be located in Quezon City based on the criteria of cost, proximity, and infrastructure with a total land area of 140 sq-m and a two-storey building area of 200 sq-m. The total fixed cost would amount to P3,085,800 from land building and office equipment. Pre-Servicing Capital Expenditure would amount to P112,380 and Venture Initiation Cost of P303,000. The total initial investment is P3,501,180. This amount would be shouldered by the 5 owners of the corporation. Stockholders would finance all of the initial investment so as not to loan from banks or other financial institutions. Looking at the financial capability of this venture, different projections were made. The sales were projected using 13 percent of the competitor's first year number of enrollees and will be increasing for the five year study period. From the projected sales, maximum of 12% of the sales will be allotted to operation expenses, minimum of 8% of sales for the reserves - actuarial estimate for two years expenditure, minimum of 60% of sales for the benefit payments and maximum of 20% of sales will be invested. There would be two kinds of investments to be made, a long-term investment and a short-term investment. Under the long-term investment would be treasury bill (15%) and special savings deposits (10%). Short-term investment would include interest bearing loans (10%), investments in shares of stocks (15%), and investments in treasury bonds (50%). Profitability ratios are computed to check whether the venture would really be financially feasible. From the computed Return on Investment (ROI), the ratios are increasing starting on the second year which implies that the assets is generating and will continually generate big profits for the stockholders. The result is the same with the Operating Profit Margin, which also showed an increasing rate. The Net Present Value (NPV) also showed a positive value which reflects an increase in wealth after implementing the project. The percentage that will make NPV equal to zero (IRR) is 374% which is much greater than the MARR which is 30%. Checking the economic feasibility of the project, it is showed that there are more benefits that can arise from the project compared to the disbenefits. This study shows that the project of putting up CLHC, a Health and Maintenance Organization, is very much viable and feasible.